Visualizing the down-regulation of hTERT mRNA expression using gold-nanoflare probes and verifying the correlation with cancer cell apoptosis. Issue 9 (20th March 2019) - Sun, Hongxiao; Hong, Min; Yang, Qiangqiang; Li, Chuan; Zhang, Guangzhi; Yue, Qiaoli; Ma, Yanhua; Li, Xia; Li, Chen-Zhong
Abstract : A locked nucleic acid-functionalized gold nanoparticle flare probe was designed to achieve in situ monitoring and regulating intracellular hTERT mRNA which also induced the apoptosis of cancer cells. Abstract : The human telomerase reverse transcriptase catalytic subunit (hTERT) is the rate-limiting subunit of the telomerase holoenzyme. Down-regulating the expression of hTERT mRNA by antisense oligonucleotides would reduce the expression of hTERT, inhibit telomerase activity, and impair the growth of cancer cells in vitro . In this work, we propose a locked nucleic acid-functionalized gold nanoparticle flare probe (AuNP-probe). After transferring these probes into cells by endocytosis of the gold nanoparticles, the binding process of the antisense locked nucleic acid with hTERT mRNA along with gene regulation can be visualized by fluorescence recovery of flare-sequences. A significant decline in hTERT mRNA levels and the hTERT content occurred in cancer cells after treatment with the AuNP-probes, and only approximately 25% of the original level of hTERT mRNA remained after 72 h. AuNP-probe treated cancer cells were arrested in the G1 phase of the cell cycle and underwent apoptosis; cell viability decreased obviously compared with that of telomerase-negative normal cells.